Application of Levan-Rich Digestate Extract in the Production of Safe-to-Use and Functional Natural Body Wash Cosmetics - Tomasz Wasilewski; Artur Seweryn; Dominika Pannert; Kinga Kierul; Marta Domżał-Kędzia; Zofia Hordyjewicz-Baran; Marcin Łukaszewicz; Agnieszka Lewińska (Molecules, 2022)
The study focused on the evaluation of the possibility of using a levan-rich digestate extract in the production of safe and functional body wash cosmetics. Model shower gels were designed and formulated on the basis of raw materials of natural origin. Prepared prototypes contained various extract concentrations (16.7; 33; 50%). A gel without extract was used as a reference. The samples were evaluated for their safety in use and functionality. The results showed that the use of high-concentration levan-rich digestate extract in a shower gel resulted in a significant reduction in the negative impact on the skin. For example, the zein value decreased by over 50% in relation to the preparation without the extract. An over 40% reduction in the emulsifying capacity of hydrophobic substances was also demonstrated, which reduces skin dryness after the washing process. However, the presence of the extract did not significantly affect the parameters related to functionality. Overall, it was indicated that levan-rich digestate extract can be successfully used as a valuable ingredient in natural cleansing cosmetics.